Utilization of Zakat and Waqf in Address Dependency Challenges of The Vulnerable in Gombe State - Muhammad, Adamu Abubakar; Bala, Babangida; Ardo, Adam Muhammad; Adam, Muhammad Bello; Mashema, Bashir Liman; Sugitanata, Arif (Al-'Aqdu: Journal of Islamic Economics Law, 2024)
The socio-economic challenges faced by vulnerable groups in Gombe State, Nigeria, underscore the need for sustainable interventions to alleviate poverty and dependency. This study examines the utilization of Zakat and Waqf as Islamic socio-economic tools to empower vulnerable populations and promote economic independence. Employing a mixed-method approach, it integrates qualitative interviews with stakeholders in Zakat and Waqf management and quantitative data on poverty and dependency rates. Findings reveal that structured and transparent administration of Zakat and Waqf can significantly enhance access to education, healthcare, and sustainable livelihoods, reducing dependency. However, challenges such as limited awareness, poor institutional frameworks, and inadequate regulatory support hinder optimal implementation. This study recommends policy reforms, institutional capacity-building, and enhanced community engagement to maximize the impact of these Islamic instruments. The research contributes to ongoing discussions on leveraging Islamic social finance to foster socio-economic equity and justice.